Functional magnetic resonance imaging data manipulation : a new approach - Alves, Victor (2009)
With constant technological advances, the organizations responsible for developing healthcare standards have made efforts to improve interoperability and information exchange between different hospital information systems. In medical imaging, images are the inputs and reports the outputs. In 2000, part 23 of the DICOM standard (Digital Imaging and Communications in Medicine Structured Report) was released as an official extension. Structured Report merges the radiologists’ and physicians’ text report and relevant images into a single report. Functional Magnetic Resonance Imaging (fMRI) is a technique of medical imaging that can make great use of the structured reports, 3D potentialities, studies comparisons and also from structuring the information. In this work we present a technique for displaying, organizing, managing and storing fMRI studies. This approach is straightforward, accessible and standardized, and aims to reduce the required time and associated costs with fMRI studies analysis.